Effects of the hydromethanolic extract of Austroplenckia populnea (Celastraceae) on reproductive parameters of male rats - Mazaro, R.; Di Stasi, L. C.; Kempinas, W. D. (Elsevier B.V., 2002)
Austroplenckia populnea (Reiss.) Lundell. was selected for this study because it has been shown that some plants from the Celastraceae family have antifertility effects. Twelve adult male rats were treated with hydromethanolic extract made from the leaves, 500 mg/kg/day, orally, for 70 days. Distilled water was administered to the control animals (n = 10). At the end of the experiment, and before killing the rats, their sexual behavior was evaluated. The number of intromissions, latencies to first mount and ejaculation, and first intromission after ejaculation were significantly reduced in the treated group, but the total number of ejaculations did not differ from the control group. The weight and histology of the reproductive organs, sperm production, spermatogenesis, prostate fructose content, cauda epidydimides duct diameter, and sperm morphology were not affected. Sperm concentration in cauda epidydimides was significantly decreased. The results showed that A. populnea has effects on male rat reproduction, affecting the sexual behavior and epididymal sperm concentration. (C) 2002 Elsevier B.V. All rights reserved.
Keywords: Austroplenckia populnea; Celastraceae; reproduction; male; sperm; rat